EVALUATION OF SEMARANG BUS RAPID TRANSIT (BRT) POLICUY IMPEMENTATION IN THE PUBLIC TRANSPORTATION IMPROVEMENT EFFORTS IN SEMARANG CITY - Rina Astuti Cahyaningrum; Aufarul Marom (Journal of Public Policy and Management Review, 2019)
To unravel the problem of congestion in the capital city of Central Java and also as a responsibility to the public, the Semarang City Government established a Bus Rapid Transit policy, as a public transportation service in the city of Semarang by using Semarang City Regulation number 12 of 2011 concerning Semarang City RPJMD 2010 - 2015 concerning the provision of Semarang Bus Rapid Transit services is 4 corridors. The purpose of this study is to analyze the evaluation of the Bus Rapid Transit policy in the city of Semarang which aims to improve public transportation and describe the inhibiting factors and drivers that influence the evaluation of BRT policies in Semarang City. The method used in this research is descriptive qualitative method. The results of the study show that in the evaluation of the Bus Rapid Transit policy in Semarang City there were problems. Factors that are considered to be an obstacle to the evaluation of the Semarang Bus Rapid Transit (BRT) policy in efforts to improve public transportation in the city of Semarang are regarding the facilities and the market facilities.